1993
DOI: 10.1111/j.1365-2265.1993.tb02137.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term efficacy of conservative surgery and radiotherapy in the control of pituitary adenomas

Abstract: Conventional external beam radiotherapy as described here combined with conservative surgery is safe and effective in the control of pituitary adenomas. These results should form a baseline for comparison with new treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
178
2
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(200 citation statements)
references
References 29 publications
(8 reference statements)
9
178
2
11
Order By: Relevance
“…The risk of developing hormone insufficiency is persistent for up to more than 15 years after radiotherapy. Brada et al reported a need for hormonal replacement therapy in 30% and 50% of patients 10 and 19 years after radiotherapy 16 . Optic neuropathy is a serious complication, but it is rare after fractionated radiotherapy to doses of 45-54 Gy; Parsons et al reported no optic nerve injuries in 106 optic nerves that received a total radiation dose of less than 59 Gy 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing hormone insufficiency is persistent for up to more than 15 years after radiotherapy. Brada et al reported a need for hormonal replacement therapy in 30% and 50% of patients 10 and 19 years after radiotherapy 16 . Optic neuropathy is a serious complication, but it is rare after fractionated radiotherapy to doses of 45-54 Gy; Parsons et al reported no optic nerve injuries in 106 optic nerves that received a total radiation dose of less than 59 Gy 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have described preoperative factors that can impact the recurrence of some pituitary lesions, 9,15,19 while others have shown the impact of postoperative radiation therapy for the prevention of recurrence. 3,20 Numerous groups have described remission rates associated with repeat transsphenoidal surgery for endocrine active and inactive pituitary lesions, 1,21 and these studies have also described the morbidity of repeat transsphenoidal surgery, but no study to date has compared the morbidity of repeat transsphenoidal surgery with that of initial transsphenoidal surgery for the variety of pathologies seen in a large pituitary practice or after prior radiation therapy.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…4,[23][24][25][26]28,33,35,37,45,[47][48][49][51][52][53]61,65 Stereotactic radiosurgery helps reduce some of the risks of conventional radiotherapy, including hypopituitarism, radiation-induced tumors, carotid stenosis, and stroke, as well as neurocognitive side effects. 1,30,38,39,56 Gamma Knife radiosurgery (GKRS) is highly effective at preventing radiographic progression of residual and recurrent adenomas. Most large radiosurgical series demonstrate a tumor control rate approaching 90%.…”
mentioning
confidence: 99%